Assessing receptiveness to change among primary healthcare providers by adopting the consolidated framework for implementation research (CFIR) - Lee Lan Low; Fathullah Iqbal Ab Rahim; Mohammad Zabri Johari; Zalilah Abdullah; Siti Hajar Abdul Aziz; Nur Ajeerah Suhaimi; Norrafizah Jaafar; Ainul Nadziha Mohd Hanafiah; Yuke Lin Kong; Siti Haniza Mahmud; Mohamad Zaidan Zulkepli; Komathi Perialathan; et al. (BMC, 2019)
Abstract Background Amid the current burden of non-communicable (NCD) diseases in Malaysia, there is a growing demand for more efficient service delivery of primary healthcare. A complex intervention is proposed to improve NCD management in Malaysia. This exploratory study aimed to assess primary healthcare providers' receptiveness towards change prior to implementation of the proposed complex intervention. Method This study was conducted using an exploratory qualitative approach on purposely selected healthcare providers at primary healthcare clinics. Twenty focus group discussions and three in-depth interviews were conducted using a semi-structured interview guide. Consent was obtained prior to interviews and for audio-recordings. Interviews were transcribed verbatim and thematically analysed, guided by the Consolidated Framework for Implementation Research (CFIR), a framework comprised of five major domains promoting implementation theory development and verification across multiple contexts. Results The study revealed via CFIR that most primary healthcare providers were receptive towards any proposed changes or intervention for the betterment of NCD care management. However, many challenges were outlined across four CFIR domains-intervention characteristics, outer setting, inner setting, and individual characteristics-that included perceived barriers to implementation. Perception of issues that triggered proposed changes reflected the current situation, including existing facilitating aspects that can support the implementation of any future intervention. The importance of strengthening the primary healthcare delivery system was also expressed. Conclusion Understanding existing situations faced at the primary healthcare setting is imperative prior to implementation of any intervention. Healthcare providers' receptiveness to change was explored, and using CFIR framework, challenges or perceived barriers among healthcare providers were identified. CFIR was able to outline the clinics' setting, individual behaviour and external agency factors that have direct impact to the organisation. These are important indicators in ensuring feasibility, effectiveness and sustainability of any intervention, as well as future scalability considerations.